2006
DOI: 10.1111/j.1439-0418.2006.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

An operative kairomonal lure for managing pine sawyer beetle Monochamus galloprovincialis (Coleoptera: Cerymbycidae)

Abstract: Monochamus galloprovincialis Olivier (Col., Cerambycidae) is a vector of the pine wood nematode, Bursaphelenchus xylophilus, causing the destructive pine wilt disease. An effective lure for monitoring and/or masstrapping would be of great interest in the management of this pine sawyer. Males and females of this species show an attractive kairomonal response to blends composed of four pheromone compounds used by Ips spp. bark beetles and two host volatiles from pines. This six-component lure is highly attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 45 publications
6
67
1
7
Order By: Relevance
“…5a) to the malespecific compound (I, Fig. 1 recorded in these analyses even though α-pinene at least is a known kairomone Ibeas et al 2007) and has been shown to elicit an EAG response from M. galloprovincialis (Álvarez, unpublished). Presumably, the antennal receptors are less sensitive to the kairomones than to the pheromones, and the concentrations of the former were too low in these analyses.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…5a) to the malespecific compound (I, Fig. 1 recorded in these analyses even though α-pinene at least is a known kairomone Ibeas et al 2007) and has been shown to elicit an EAG response from M. galloprovincialis (Álvarez, unpublished). Presumably, the antennal receptors are less sensitive to the kairomones than to the pheromones, and the concentrations of the former were too low in these analyses.…”
Section: Resultsmentioning
confidence: 97%
“…Dispensers for bark beetle semiochemicals and host compounds were as described previously by Pajares et al (2004) and Ibeas et al (2007). Thus, racemic ipsenol, racemic ipsdienol, 2-methyl-3-buten-2-ol, and ∼80%-(-)- Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining bark beetle pheromones and host volatiles on the same traps has synergized attraction of Scolytinae (Borden et al, 1980;Shore & Lindgren, 1996) as well as Cerambycidae (Billings, 1985;Allison et al, 2001Allison et al, , 2003Allison et al, , 2004de Groot & Nott, 2004;Pajares et al, 2004;Ibeas et al, 2006;Costello et al, 2008;Miller et al, 2011Miller et al, , 2015a. Similarly, combination of longhorn beetle pheromones and host volatiles synergizes attraction of cerambycids (Nakamuta et al, 1997;Fettköther et al, 2000;Reddy et al, 2005;Silk et al, 2007;Nehme et al, 2009;Sweeney et al, 2010Sweeney et al, , 2014Pajares et al, 2010;Teale et al, 2011;Allison et al, 2012;Hanks et al, 2012;Macias-Samano et al, 2012;Miller et al, 2015b;Ryall et al, 2015; but see Pajares et al, 2010).…”
Section: Semiochemicals Lures and Release Ratesmentioning
confidence: 99%